Methods for Improvement of Education of Parasitology & Mycology\'s Module Based on Viewpoints of Medical Students in Babol University of Medical Sciences - Afshin Khani; Salman Ghaffari; Narges Kalantari; Zahra Sheikh (Babol University of Medical Sciences, 2014)
BACKGROUND AND OBJECTIVES: Effective learning of parasitology and mycology has been always a challenge for medical students. Attention toward students' viewpoints can develop the education of this course. This study aimed to assess the viewpoints of medical students about the methods for improvement of education of medical parasitology and mycology's module. METHODS: This cross-sectional study was carried out on medical students at Babol University of Medical Sciences in autumn 2010. The 2nd, 3rd and 4th year of medical students who passed the course, participated as easy and available allocation procedure and filled a self-constructed questionnaire. Questionnaire, s validity and reliability were confirmed with a Cronbach alpha 0.7 and expert's opinions, respectively. Chi-square was used for data analysis. FINDINGS: In overall, 91 participants filled the questionnaires (response rate = 76%) fifty seven (62.6%) were female and 34 (37.4%) were male. The mean age of participants was 21.66±38 years. Students believed that using of educational videos has the best effect on learning outcome. Development in the quality of training classes and dissociation of the module to separate sections should be the short-term and long-term solutions for improvement of the education respectively. There was no significant relationship between sex, educational level of students and their viewpoints (p>0.05). CONCLUSION: Reconsideration of parasitology and mycology curriculums and new training methods such as application of educational videos and internet are offered.